Labial frenum attachment and its association with oral hygiene status in patients reporting to a local tertiary care dental hospital - Maqbool, Maha; Usman Manzoor; Ahmad Danyal; Abrar Humayun; Nuvaira Ijaz (Journal of University Medical & Dental College, 2024)
Background and Objective: The labial frenum plays an important role in providing attachment between the lip and the alveolar process and at the same time contributes significantly to the maintenance of proper oral hygiene. The main objective of this study was to evaluate the labial frenum attachment in both the upper and lower jaw and investigate its potential association with the age, gender, and oral hygiene condition among individuals presenting to a local tertiary care hospital Methodology: This cross-sectional study was carried out at Lahore Medical and Dental College, Lahore over a period of six months. A total of 360 patients were included in the study after obtaining permission from the institutional ethical review committee The labial frenum type was identified and recorded for both mandible and maxilla. The oral hygiene status was accessed using the oral hygiene index (simplified). Assessment of both frenal attachment and oral hygiene was done by the same examiner to minimize the chances of any bias. Results: Our study included a total of 360 patients with 47% (171) males and 53% (189) females. Moreover, in our study, the most common type of frenal attachment was gingival (65%), followed by mucosal (19%) and less commonly the papillary (11%) and papillary penetrating (6%) types. A strong association was observed between the frenal attachment type and oral hygiene status among our study population (P value= 0.00). Conclusion: The association of frenal attachment with oral hygiene and gender is statistically significant.